Numerical investigation on thermohydraulic and exergy performance enhancement for triplex concentric tube heat exchanger using MXene nanofluids - Gaur S.K.; Sahoo R.R.; Sarkar J. (My University, 2025)
This study delves into heat transfer characteristics and fluid flow within a triplex tube heat exchanger (TTHX), employing water- and water-based 1% v/v. MXene and Al2O3 nanofluids. It scrutinizes the impact of the Reynolds number on various performance metrics such as heat transfer coefficients, performance evaluation criteria (PEC), effectiveness, exergy loss, and entropy generation. Employing a 3D RNG/k-ε model with improved wall treatment, which has been validated by empirical correlation data available in the literature, the research uncovers that the utilization of MXene nanofluid led to a 12.51% increase in heat transfer coefficients compared to the Al2O3 nanofluid and a 20% increase as compared to water, when deployed in a counter-flow configuration of the TTHX. Notably, the PEC and effectiveness graph indicate that MXene nanofluid exhibits a substantial increase of 21.73% and 29.71% over Al2O3 nanofluid at a Reynolds number of 6800 and 4400. Additionally, the exergy loss and entropy generation with Mxene nanofluid is reduced by 10.5% and 33.34% compared to Al2O3 nanofluid. Consequently, MXene nanofluids have the potential to significantly enhance the overall performance of a triplex tube heat exchanger compared to conventional fluids. © The Author(s), under exclusive licence to Iranian Society of Environmentalists (IRSEN) and Science and Research Branch, Islamic Azad University 2024.